2014
DOI: 10.1371/journal.pone.0105790
|View full text |Cite
|
Sign up to set email alerts
|

Development, Validation and Clinical Evaluation of a Low Cost In-House HIV-1 Drug Resistance Genotyping Assay for Indian Patients

Abstract: Human Immunodeficiency Virus-1 (HIV-1) drug resistance genotyping assay is a part of clinical management of HIV-1 positive individuals under treatment with highly active antiretroviral therapy (HAART). Routine monitoring of drug resistance mutations in resource limited settings like India is not possible due to high cost of commercial drug resistance assays. In this study we developed an in-house, cost effective HIV-1 drug resistance genotyping assay for Indian patients and validated it against the US-FDA-appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The CDC supplies WHO-designated and CDC-supported President's Emergency Plan for AIDS Relief (PEPFAR) Genotyping Laboratories with the ATCC HIV-1 Drug Resistance Genotyping kit (46) for drug resistance testing. Many experienced genotyping laboratories have developed their own in-house amplification and sequencing protocols (11,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), including identification of minor viral variants that are normally missed by commercial genotyping kits (57-61). All of these approaches generally include smaller and more restricted regions for testing HIV-1 drug resistance.…”
mentioning
confidence: 99%
“…The CDC supplies WHO-designated and CDC-supported President's Emergency Plan for AIDS Relief (PEPFAR) Genotyping Laboratories with the ATCC HIV-1 Drug Resistance Genotyping kit (46) for drug resistance testing. Many experienced genotyping laboratories have developed their own in-house amplification and sequencing protocols (11,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), including identification of minor viral variants that are normally missed by commercial genotyping kits (57-61). All of these approaches generally include smaller and more restricted regions for testing HIV-1 drug resistance.…”
mentioning
confidence: 99%
“…The cost estimate represents all the inputs required for performing HIVDR testing including; capital, personnel, reagents, consumables, quality assurance program and service contracts for the laboratory equipment for performing 1000 tests per year. Previous studies did not include all cost categories, making it difficult to compare costs for offering drug resistant tests across many laboratories ( Acharya et al , 2014 ; Alemán et al , 2015 ; Inzaule et al , 2013 ; Novitsky et al , 2015 ). In this study, we offer a framework for performing laboratory cost analyses that makes it easy to compare cost categories between different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies performed in other parts of the world found considerably lower reagents and consumables costs than those estimated by this study. For instance, the costs reported in India and Cuba were $85.00 and $87.80, respectively ( Acharya et al , 2014 ; Alemán et al , 2015 ). Conversely, one study reported higher reagent costs than those found in the present study; the estimated cost was $139.75 per test ( Novitsky et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations